The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.32582/aa.58.3.2
|View full text |Cite
|
Sign up to set email alerts
|

The abundance and speciation of mercury in the Adriatic plankton, bivalves and fish – a review

Abstract: This article presents an overview of available research on mercury speciation in the most studied biota of the Adriatic Sea as a specific biogeochemical subunit of the Mediterranean. We present current knowledge about mercury concentration, speciation, spatial distribution and temporal changes in plankton, bivalves and fish from the Adriatic Sea. Results from mercury speciation studies in marine organisms are used to describe the extent of mercury bioaccumulation in the Adriatic Sea. Mercury biogeochemical cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 116 publications
(227 reference statements)
0
4
0
Order By: Relevance
“…Benthic organisms from neritic habitats are the most highly represented group. As expected, there are a large number of Mediterranean mussel ( Mytilus galloprovincialis ) samples, which are frequently used as a favoured bioindicator 27,33,34 .…”
Section: Data Recordsmentioning
confidence: 56%
See 3 more Smart Citations
“…Benthic organisms from neritic habitats are the most highly represented group. As expected, there are a large number of Mediterranean mussel ( Mytilus galloprovincialis ) samples, which are frequently used as a favoured bioindicator 27,33,34 .…”
Section: Data Recordsmentioning
confidence: 56%
“…Differences in fish habitat, fish age/size, and the possibility of variable environmental mercury loadings make an exact assessment difficult without detailed modelling. A recent review of mercury speciation in the Adriatic biota showed no significant differences in fish mercury with time 27 . Possible sample contamination and the use of mercury-contaminated acids for sample digestion might have caused errors in older studies since results were often not corrected for blanks (this information is not commonly reported in older studies).…”
Section: Data Recordsmentioning
confidence: 99%
See 2 more Smart Citations